Spatio-temporal variations in past extreme tree-growth reduction events and their resilience components over northern high-latitude regions - Tei, Shunsuke (Frontiers in Forests and Global Change, 2025)
IntroductionTerrestrial forest ecosystems in northern high-latitude regions are crucial to the global carbon cycle and climate system but vulnerable to climate change. Global warming has contributed to increased forest decay and mortality in this region. Despite decades of research on temporal variability, the long-term stability and regional representativeness of resilience components remain poorly understood, limiting our ability to predict future forest resilience. Hence, this study aimed to examine past extreme tree-growth reduction (EGR) events and the associated resilience components across northern high-latitude regions.MethodsThis study estimated the past EGR events and associated resilience components using the tree-ring width index (RWI) data from 523 International Tree-Ring Data Bank (ITRDB) sites across the northern high-latitude regions and analyzed the spatial and temporal variations in resilience.ResultsNo significant regional differences were found in the frequency of EGR events over the past several hundred years; however, the resilience components exhibited large spatial variations with significant regional differences. The regional-averaged resilience (Rs) over the entire analysis period was lower in Canada than in Alaska, Eurasia, or Europe, suggesting a possible higher vulnerability to EGR events in Canada.DiscussionThe high vulnerability in Canada was not attributed to the large reduction in growth during the EGR event but to the small amount of recovery (Rc) after the event. As almost no significant temporal changes were observed with respect to regional differences in the resilience components over the four analysis periods, that is, (i) pre-1700, (ii) 1701–1800, (iii) 1801–1900, and (iv) post-1900, the resilience components estimated in this study could be considered as representative values for each region, and the pattern of regional difference remained relatively consistent from the past to the present and likely into the future. These results are crucial to understand future tree and forest dynamics in the high latitudes of the Northern Hemisphere, particularly regarding risks associated with tree decline and mortality due to climate extremes and other disturbance factors.